Theoretical Study of Nuclear Density Distributions and Elastic Electron Scattering form Factors for Some Halo Nuclei - R. Ridha, Arkan; K. Suhayeb, Mustafa (Iraqi Journal of Science, 2021)
The nuclear matter density distributions, elastic electron scattering charge formfactors and root-mean square (rms) proton, charge, neutron and matter radii arestudied for neutron-rich 6,8He and 19C nuclei and proton-rich 8B and 17Ne nuclei. Thelocal scale transformation (LST) are used to improve the performance radial wavefunction of harmonic-oscillator wave function in order to generate the long tailbehavior appeared in matter density distribution at high . A good agreement resultsare obtained for aforementioned quantities in the used model.